Obstacles to Early Diagnosis of Gaucher Disease - Nishimura S; Ma C; Sidransky E; Ryan E (Therapeutics and Clinical Risk Management)
Samantha Nishimura,* Charis Ma,* Ellen Sidransky, Emory Ryan National Human Genome Research Institute, National Institutes of Health, Bethesda, MD, USA*These authors contributed equally to this workCorrespondence: Ellen Sidransky, National Human Genome Research Institute, National Institutes of Health, Building 35A -1E623 Convent Drive, MSC 3708, Bethesda, MD, 20892-3708, USA, Tel +1-301-451-0901, Fax +301-402-6438, Email sidranse@nih.govAbstract: Gaucher disease (GD) is a rare lysosomal storage disorder resulting from a deficiency of the lysosomal enzyme glucocerebrosidase caused by biallelic variants in the GBA1 gene. Patients may present with a wide spectrum of disease manifestations, including hepatosplenomegaly, thrombocytopenia, bone manifestations, and in the case of GD types 2 and 3, neurodegeneration, cognitive delay, and/or oculomotor abnormalities. While there is no treatment for neuronopathic GD, non-neuronopathic manifestations can be efficiently managed with enzyme replacement therapy or substrate reduction therapy. However, many patients with GD experience a lengthy diagnostic odyssey, which can negatively affect their access to care and clinical outcomes. The cause of this diagnostic delay is multifaceted. Since genotype/phenotype correlations in GD are not always clear, it is difficult to predict the presence, severity, and onset of clinical manifestations. This heterogeneity, combined with the molecular complexity of the GBA1 locus, low disease prevalence, and limited knowledge of GD among providers serves as a barrier to early diagnosis of GD. In this review, we discuss such obstacles and challenges, considerations, and future steps toward improving the diagnostic journey for patients with GD.Keywords: Gaucher disease, newborn screening, diagnosis